Застосування практики рішень Європейського суду з прав людини у кримінальному провадженні України - Соловйова, О. Є.; Soloviova, O. Ye.; Олена Соловйова (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 1 (108), ч. 1. - С. 354-364, 2025)
Статтю присвячено аналізу процесу застосування практики рішень Європейського суду з прав людини та Конвенції про захист прав людини і основоположних свобод у кримінальному провадженні України. Розглянуто сучасні проблеми імплементації європейських стандартів у національну судову систему та досудове розслідування кримінальних проваджень, зокрема невизначеність правового тлумачення, юридичні та процедурні перешкоди. Дослідження базується на аналізі судової практики, порівняльному правовому аналізі та вивченні наукових джерел, що дозволило визначити основні напрями реформування кримінального провадження з метою підвищення ефективності захисту прав людини. Результати дослідження свідчать про необхідність адаптації національного законодавства до європейських стандартів та вдосконалення процесуальних норм, що сприятиме об’єктивному досудовому розслідуванню та судовому розгляду. Дослідження містить практичні рекомендації щодо розв’язання наявних проблем, які можуть стати основою для подальших реформ у кримінальному процесі.

The article analyses the process of applying the European Court of Human Rights case law and the Convention for the Protection of Human Rights and Fundamental Freedoms of 1950 in criminal proceedings in Ukraine. The basic principles arising from the jurisprudence of the European Court of Human Rights and their impact on national legislation and court practice are investigated. Particular attention is paid to the issues of observance of the right to a fair trial, presumption of innocence, prohibition of torture and effective investigation of human rights violations. The key cases of the European Court of Human Rights against Ukraine, which have determined the directions of reforms in the field of criminal justice, are analysed. The problems of implementation of the European Court of Human Rights case law in the criminal justice system of Ukraine, in particular, the formal approach to the use of case law, the lack of an effective mechanism for the execution of judgments and insufficient training of law enforcement and law enforcement agencies are investigated. The following prospects for improving the application of the European Court of Human Rights case law in criminal proceedings in Ukraine are identified: 1) the amendments to the Criminal Procedure Code of Ukraine to comply with European standards, in particular, with regard to the right to a fair trial, the presumption of innocence, protection against torture and unlawful detention, ill-treatment, etc.; 2) the development of recommendations to improve the training of judges, prosecutors, lawyers and pre-trial investigation bodies; 3) the strengthening of control over the observance of human rights, the reasonableness of the time limits during the pre-trial investigation, and fair and lawful trial; The following prospects for improving the application of the European Court of Human Rights case law in criminal proceedings in Ukraine are identified: 4) the improvement of procedures for verification, evaluation and examination of evidence in order to protect the defence from unlawful actions of the prosecution; 5) the introduction of mechanisms for the effective implementation of judgments of the European Court of Human Rights in individual cases; 6) the provision of adequate funding and resources to law enforcement and law enforcement agencies.
Application of the European Court of Human Rights case law in the criminal proceedings in Ukraine
Keywords: кримінальне провадження; Європейський суд з прав людини; кримінальне судочинство; права людини; кримінальний процес; міжнародне право; судова практика; імплементація рішень; criminal proceedings; European Court of Human Rights; criminal justice; human rights; criminal procedure; international law; case law; implementation of judgments